Otimização de parâmetros da síntese de sílica SBA-15 para viabilizar o escalonamento. - Souza Teixeira, Nathalia; Viana Sales , Rafael; Iara Soares de Mello, Mariele; Berenice Castellã Pergher, Sibele; José Volpi Eusébio de Oliveira , Fernando (XIV Encontro de Catálise do Norte, Nordeste e Centro-Oeste, 2024)
In the present work, the focus was on scaling up the synthesis of mesoporous SBA-15 material. To achieve this, the research explored reducing the reaction volume, making the scale-up feasible. The experiment involved decreasing the volume of water and hydrochloric acid to half, one-third, and two-thirds of the original amount. The resulting materials were carefully characterized and compared with SBA-15 synthesized under standard conditions.The approach used was based on acidic hydrolysis, where the team began by dissolving the directing agent, a P123 copolymer, into a 37% HCl solution. Afterward, they introduced the silicon precursor, tetraethyl orthosilicate (TEOS), keeping the mixture under constant stirring at 35°C. They focused on two key parameters: the aging time and the reduced volume of the liquid phase.A variety of characterization techniques, including X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), nitrogen adsorption-desorption (BET), and Scanning Electron Microscopy (SEM), were employed to analyze the materials. The results, particularly those shown in figure 1, confirmed the successful formation of the SBA-15 structure and highlighted the viability of scaling up the synthesis process.